CLASSIFYING "CULTURE" IN INDONESIAN SECONDARY PUBLIC EDUCATION EFL TEXTBOOKS - Saiful Akmal; Nashriyah Nashriyah; Najmiatul Fauza; Chamisah Chamisah; Khairiah Syahabuddin (IJEE (Indonesian Journal of English Education), 2023)
ABSTRACTThis study investigates the categorization of cultural materials and the sense of the culture of two "Bahasa Inggris 2017 updated edition" English textbooks for grades X and XI in senior high school in Indonesian secondary education. This study examines which cultures are exemplified in the textbooks and how they are characterized. The study's design follows a qualitative descriptive design through content analysis. Both the "categories of culture" approach of Cortazzi and Jin (1999) and the "sense of culture" approach of Adaskou, Britten, and Fahsi (1990) were used in the present study. The data showed that the Bahasa Inggris tenth-grade textbook focused more on source culture instead of the target culture and international culture. Nonetheless, in the Bahasa Inggris eleventh-grade textbook, the target culture is more dominant than the source and international cultures. In both books, the pragmatic sense dominated the aesthetic, semantic, and social sense. This study also uncovered an imbalance in the number of cultural categories exhibited. This study proposes that writers of EFL textbooks should accommodate a balanced representation of source culture, target culture, and international culture, as well as provide an excellent four-cultural sense in the textbooks.ABSTRAKPenelitian ini menyelidiki kategorisasi bahan budaya dan pemahaman budaya dari dua buku teks bahasa Inggris "Bahasa Inggris 2017 edisi terbaru" untuk kelas X dan XI di sekolah menengah atas dalam pendidikan menengah di Indonesia. Penelitian ini menguji budaya mana yang diwakili dalam buku teks dan bagaimana budaya tersebut dikarakterisasi. Desain penelitian ini mengikuti desain deskriptif kualitatif melalui analisis konten. Pendekatan "kategori budaya" dari Cortazzi dan Jin (1999) serta pendekatan "pemahaman budaya" dari Adaskou, Britten, dan Fahsi (1990) digunakan dalam penelitian ini. Data menunjukkan bahwa buku teks bahasa Inggris kelas sepuluh lebih fokus pada budaya sumber daripada budaya target dan budaya internasional. Namun, dalam buku teks bahasa Inggris kelas sebelas, budaya target lebih dominan daripada budaya sumber dan budaya internasional. Pada kedua buku tersebut, pemahaman pragmatik mendominasi pemahaman estetika, semantik, dan sosial. Penelitian ini juga menemukan ketidakseimbangan dalam jumlah kategori budaya yang ditampilkan. Penelitian ini mengusulkan bahwa penulis buku teks bahasa Inggris sebagai bahasa asing sebaiknya menyertakan representasi yang seimbang dari budaya sumber, budaya target, dan budaya internasional, serta menyediakan pemahaman budaya yang baik dalam empat aspek dalam buku teks.How to Cite: Akmal, S., Nashriyah, Fauza, N., Chamisah, Syahabuddin, K. (2023). Classifying "Culture" in Indonesian Secondary Public Education EFL Textbooks. IJEE (Indonesian Journal of English Education), 10(1), 83-105. doi:10.15408/ijee.v10i1.29924